Kepatuhan Penggunaan Masker pada Kegiatan Shalat Tarawih di Masjid Al Hikmah Jakarta Pasca Pencabutan Kebijakan PPKM - Acintya Wika Sitakusuma; Helen Andriani (Jurnal Medika Hutama, 2023)
Background: Managing the spread of COVID-19 in Indonesia has been carried out massively since 2021-2022. Implementation of policies such as 3M, 3T, vaccination, discipline, compact, and consistent were taken to maintain this control. In fact, cases of the spread of COVID-19 were under controlled until the Government of Indonesia finally began to loosen policies by revoking one of the policies in the form of PPKM in December 2022. Following that time of the community's free time activities, also welcomed by the arrival of the month of Ramadan in which the majority of people can perform the usual tarawih prayer activities freely in congregation with due observance of health protocols, including the use of masks. Therefore, this paper aims to look at compliance with the use of masks during Tarawih prayer activities at a mosque in Jakarta in connection with the revocation of the PPKM policy. Method: Simple quantitative descriptive is used so that the data can be analyzed and studied independently to fulfill the research objectives. Results: It is found that there is non-compliance with the use of masks in people who perform Tarawih prayers as many as 93% of respondents at the Al Hikmah Mosque, East Jakarta. The research is based on demographic factors and the behavior of the people who become the object of research, including in the form of people's understanding of regulations and their compliance with regulations. Conclusion: From the results in the form of non-compliance with the use of masks in the community with the activities mentioned earlier, it is hoped that there will be additional socialization on the use of masks as an implementation of health protocols so that the level of public awareness in facing the risk of COVID-19 can be maintained so that the spread of COVID-19 can continue to be controlled before the COVID-19 pandemic is declared over.